Bell Media Must Restore Local Sports at CTV Montreal : QCGN - Quebec Community Groups Network (QCGN) (2017)

Re: CRTC 2015-421-4 : A Review of the Policy Framework for Local and Community Television Programming - Rodgers, Guy (2016)

Re: A Review of the Policy Framework for Local and Community Television Programming : CRTC 2015-421 - Rodgers, Guy (2015)

Re: 2013-1746-2 : Non-compliance Complaint Regarding MATV by Sabine Friesinger (OBCI) - Rodgers, Guy (2014)

Update on Community TV - English Language Arts Network (ELAN) (2014)

CRTC Must Oblige Vidéotron to Restore English-language Community Television Station - Quebec Community Groups Network (QCGN) (2013)

CRTC Must Oblige Vidéotron to Restore English-language Community Television Station : Attention News Directors, Television, and Arts Reports - Quebec Community Groups Network (QCGN) (2013)

CRTC Decision on CBC License Renewal Good News for English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2013)
Keywords: Official Language Minority Community (OLMC)

CRTC Decision on CBC License Renewal Good News for English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2013)

ELAN Speech to CRTC for Community TV Channel Hearing PN 2009-661 - Rodgers, Guy (2010)

Review of Key Documents on the English-language Film/TV/Media Production Industry in Quebec for the English-language Arts Network of Quebec - Magnetic North Associates (English-Language Arts Network (ELAN), 2010)
Responding to anecdotal evidence from their members, the Quebec chapters of ACTRA and DGC commissioned a major study of English-language production in Quebec based on CAVCO data (Appendix I). This 2008 report was titled “Going…Going…Gone: The Decline of English-language Production in Quebec 1996-7 to 2006-7”, and it demonstrated several long term trends in domestic production.
Keywords: Official Language Minority Community (OLMC)

Survey of the English-language Film/TV/Media Industry in Quebec for the English-language Arts Network of Quebec with funding from Telefilm Canada - Magnetic North Associates (English-Language Arts Network (ELAN), 2010)
There has been a significant shift in the demographic profile of the English-Quebec production industry since the last similar survey of English-Quebec producers in 2003. Today’s industry is more female, has fewer immigrants, and is much more bilingual. Sixty two per cent say they speak fluent French. This demographic shift may be caused by the departure of members of the industry with poorer French language skills or an increase in language skills.
Keywords: Official Language Minority Community (OLMC)

Re: CRTC 2009-661 : Review of Community Television Policy Framework - Rodgers, Guy (2010)

ELAN Response to Questions Raised by the CRTC at the Community TV Hearing, April 30, 2010 - English Language Arts Network (ELAN) (2010)

Notes for a Speech from ELAN to the CRTC at Hearing 2009-411 - Rodgers, Guy (2009)

[Letter Regarding the Canada Media Fund and the Official Languages Act (OLA)] - Jordan, Don; Gibbons, Rodney (2009)

Re: CRTC 2009-411 : Policy Proceeding on a Group-based Approach to the Licensing of Television Services and on Certain Issues Relating to Conventional Television - Rodgers, Guy (2009)

Re: CRTC 2009-437 - Rodgers, Guy (2009)

Local Television Support for the Official-language Minority in Quebec - Magnetic North Associates (2009)
The Anglophone minority doesn’t lack access to English-language channels via satellite and cable distribution, but it is underserved in “regional reflection” and “local expression”. That is especially the case for the 200,000 Anglophones outside the greater Montreal area who have virtually no “regional reflection”. The reason for this inadequate regional programming can be traced to the lack of regional services available to the official language minority community (OLMC) in Quebec. There is no English-language educational channel, similar to TFO in Ontario, nor is there an English regional channel, or community channel.

Objet : CRTC 2009-196 - Demandes de renouvellement de license présentées par la Société de Télédiffusion du Québec et par Canal Savoir - Rodgers, Guy (2009)

Notes for a Speech from ELAN to the CRTC at Hearing 2009-113 - Cox, Kirwan (2009)

Re: CRTC 2009-113 - Rodgers, Guy (2009)

Response to Commissioners Arpin. von Finckenstein, and Katz about Videotron, VOX, and the Official Language Minority in Quebec - English Language Arts Network (ELAN) (2009)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1991)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1987)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1985)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1984)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1982)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1982)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1979)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1978)

The Royal Commission on Broadcasting - The Canadian Home and School and Parent-Teacher Federation (1956)
The Canadian Home and School and Parent-Teacher Federation, representing 274,693 members organized in 3,672 local associations in nine provincial federations across Canada, (Newfoundland is not presentl:y organized as a Provincial Federation) is pleased to submit this statement of our views with respect to broadcasting in Canada under the terms of Order in Council P.C.1955-1796 of December 2nd,1955